Efektifitas Sosialisasi Perlindungan Hukum Terhadap Permasalahan Hukum Bagi Guru Di Kota Semarang - Budoyo, Sapto (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
Legal protection for teachers in carrying out their professional duties is very much needed considering the many criminal and civil cases that often befall teachers. This became the basis for the author to conduct a study on the main problem of how the effectiveness of the socialization of legal protection against legal problems for teachers in the city of Semarang. The research was conducted using an empirical juridical approach that relied on data obtained from the field which was then analyzed using data triangulation to achieve the expected results. The results of the study show that intoe able to find out the effectiveness of the socialization of legal protection against legal problems for teachers in the city of Semarang, the authors have conducted a study of the number of socializations regarding legal protection for teachers that have been carried out by the Semarang City PGRI team for the last five years where the number found is a number 17 , of course, this number is quite good compared to other regions, which of course also influences the increasing understanding of legal protection for teachers in the city of Semarang.